Antiviral Therapy Targeting Viral Polymerase - Tsai, Ching-Hsiu; Lee, Pei-Yu; Stollar, Victor; Li, Mei-Ling (Current Pharmaceutical Design, 2006)
Viral DNA and RNA polymerases are enzymes, which are responsible for copying the genetic materials of viruses and are therefore central components in the life cycles of viruses. The polymerases are essentially required for the replication of viruses. The reverse transcriptase (RT) of the retroviruses and the hepadnaviruses is the sole viral enzyme required for the synthesis of DNA from viral RNA. Viral polymerases are therefore an extremely favorable target for the development of antiviral therapy. The success of anti-HIV-1 therapy using inhibitors specifically targeting HIV RT suggests that other viral polymerases can be the valid molecular targets for the design of antiviral drugs. Intensive structural and functional studies of viral polymerases have been conducted and have opened new avenues for the development of more effective antiviral therapy. This review summarizes the insights gained from recent structural and functional studies of antiviral agents, which target viral polymearses. The primary focus will be on hepatitis C virus (HCV), herpesviruses, HIV, hepatitis B virus (HBV) and influenza virus.
Keywords: HBV polymerase